Antigenic variation in clones of animal-infective Trypanosoma brucei derived and maintained in vitro - Doyle, J.J.; Hirumi, H.; Hirumi, K.; Lupton, E.N.; Cross, G.A.M. (Cambridge University Press, 1980)
Eighteen clones of variable antigen type 052 of Trypanosoma brucei stock S. 427 were derived and maintained as animal-infective bloodstream forms in vitro for up to 60 days of cultivation. The antigenic composition of such clones was monitored weekly by immunofluorescent analysis of viable trypanosomes, using antisera raised to isolated variant-specific surface glycoproteins of both 052 and a variable antigen type (221) which consistently appeared in the first relapse population of type 052 in vitro. The appearance of new variants was detected in 9 of the 18 clones 18–46 days following initiation of the clone and variable antigen type 221 was found in all 9 clones. On one or more occasions in 8 of such clones, viable trypanosomes were found which did not react with either antiserum but were mouse-infective on the 4 occasions tested and probably represent other variable antigen types. The process of antigen, variation in vitro appears to resemble the process in vivo except that new variant types are detected earlier in vivo. This possibly results from different growth rates of the trypanosomes in vivo and in vitro, together with the fact that elimination of the initial variant population by the host's immune response facilitates the detection of newly arising variable antigen types in vivo.